Financial reporting frequency, information asymmetry, and the cost of equity - Fu, Renhui; Kraft, Arthur; Zhang, Huai (Journal of Accounting and Economics, 2012)
Using hand-collected data on firms’ interim reporting frequency from 1951 to 1973, we examine the impact of financial reporting frequency on information asymmetry and the cost of equity. Our results show that higher reporting frequency reduces information asymmetry and the cost of equity, and they are robust towards considerations of the endogenous nature of firms’ reporting frequency choice. We obtain similar results when we focus on mandatory changes in reporting frequency. Our results suggest the benefits of increased reporting frequency.